1998
DOI: 10.1164/ajrccm.158.5.9803027
|View full text |Cite
|
Sign up to set email alerts
|

Dual Action of iNOS-derived Nitric Oxide in Allergen-induced Airway Hyperreactivity in Conscious, Unrestrained Guinea Pigs

Abstract: Using a guinea pig model of acute allergic asthma, we recently established that a deficiency of nitric oxide (NO) contributes to airway hyperreactivity (AHR) after the early asthmatic reaction (EAR) and that restoration of NO activity may contribute to the (partial) reversal of AHR after the late asthmatic reaction (LAR). In the present study, we investigated the role of iNOS-derived NO in the regulation of AHR to histamine after the LAR. Inhalation of a selective dose of the specific iNOS inhibitor aminoguani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 44 publications
3
67
1
8
Order By: Relevance
“…For example, it has been reported that pretreatment of mice with specific iNOS inhibitors decreases airway eosinophilia in response to allergen stimulation, either by blocking chemokine expression (71) or by delaying the efflux of eosinophils from the bone marrow (72). In contrast, other investigators have been unable to demonstrate a protective effect of iNOS inhibition on pulmonary leukocytosis (73)(74)(75), and iNOSdeficient mice paradoxically exhibit enhanced lung injury in response to OVA challenge (76). Our demonstration that bilirubin treatment does not alter chemokine levels and is associated with an increase (as opposed to a decrease) in the number of circulating eosinophils makes it unlikely that the effects of this bile pigment on airway inflammation are related to alterations in iNOS expression.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, it has been reported that pretreatment of mice with specific iNOS inhibitors decreases airway eosinophilia in response to allergen stimulation, either by blocking chemokine expression (71) or by delaying the efflux of eosinophils from the bone marrow (72). In contrast, other investigators have been unable to demonstrate a protective effect of iNOS inhibition on pulmonary leukocytosis (73)(74)(75), and iNOSdeficient mice paradoxically exhibit enhanced lung injury in response to OVA challenge (76). Our demonstration that bilirubin treatment does not alter chemokine levels and is associated with an increase (as opposed to a decrease) in the number of circulating eosinophils makes it unlikely that the effects of this bile pigment on airway inflammation are related to alterations in iNOS expression.…”
Section: Discussioncontrasting
confidence: 55%
“…Interestingly, iNOS-derived NO per se had no proinflammatory effects in the airways and even decreased airway responsiveness to methacholine [42]. Using in vivo studies in our guinea pig model of allergic asthma, we have previously demonstrated that iNOS-derived NO, aside from promoting airway inflammation and epithelial damage, also had some beneficial effect on allergen-induced AHR after the LAR, by partially attenuating the hyperresponsiveness due to its bronchodilating effect [10]. Remarkably, treatment with a selective iNOS inhibitor did not affect allergen-induced AHR in asthmatic patients, although levels of exhaled NO were markedly reduced [43].…”
Section: +mentioning
confidence: 88%
“…Using a guinea pig model of acute allergic asthma, we have previously demonstrated that both NO, derived from iNOS which is induced during the LAR [4,10], and superoxide are involved the development of AHR after the LAR, presumably by the formation of peroxynitrite [11]. Thus, incubation of perfused tracheal preparations with L-NAME, as well as superoxide dismutase, fully reverted the AHR after the LAR in these preparations [11].…”
Section: Cell and Animal Studies H Maarsingh Et Almentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, both in vivo and ex vivo studies using the same species indicate that a deficiency of both epithelial and neuronal cNOS-derived NO underlies the development of AHR following the allergen-induced early asthmatic reaction ( fig. 1) [77,96,97]. A deficiency of cNOS activity and endogenous bronchodilating NO contributing to AHR was also demonstrated after repeated allergen challenge of sensitised guinea pigs [98,99].…”
Section: Acute Modulation Of Ahrmentioning
confidence: 91%